Psychosemantic Research of the Psychological Well-Being of Artists - Elena A. Vakarina (Lomonosov Moscow State University, 2024)
Background. Psychological well-being ensures the positive functioning of the artist's personality, which includes internal (subjective) and external (objective) factors. The dynamism of the art market, instability of demand and orders, displacement of individuality by mass art lead to emotional tension, increased anxiety and, as a consequence, to a decrease in the level of well-being and to the growth of psychological insecurity of artists. Psychosemantic space reflects social representations that reveal the most significant and prioritised sources of maintaining an optimal level of psychological well-being for artists. Objectives. The aim of the study was to identify and describe meaning groups of sources of psychological well-being of artists. Study Participants. The research participants were 57 people aged 19 to 60. Data processing was carried out by content analysis. The criterion for selecting the sample was the profile education obtained in a specialized secondary or higher education institution. Methods. A survey with an open type of questions about well-being among artists was conducted. Data processing was carried out by content analysis and by the method of condensation of meaning. Results. The most frequently occurring semantic groups of factors of psychological well-being are identified. External factors of psychological well-being of artists include environment, relationships, quality of life and educational environment. The internal factors of artists' psychological well-being include: health and self-perception. Conclusions. The selected semantic groups are reflections of emotional, communicative and behavioral components of external and internal sources of psychological well-being of artist. They determine the psychosemantic space of the studied phenomenon. Practical application of the results. The findings give rise to the study of social representations of artists' psychological well-being. These results can be used by artists to optimize their current state; by psychologists and teachers to develop psycho-corrective and psycho-prophylactic programmes aimed to increase the level of well-being through the actualization of artists' personal resources.